Original articleThe neuroprotective effect of long-term n-3 polyunsaturated fatty acids supplementation in the cerebral cortex and hippocampus of aging rats - Firląg, Maciej; Kamaszewski, Maciej; Gaca, Katarzyna; Adamek, Dobrochna; Bałasińska, Bożena (Folia Neuropathologica, 2013)
The purpose of this study was to determine whether hippocampus and cerebral cortex fatty acids (FA) composition can be altered as a result of n-3 enriched diet, or modifications in FA can affect the age-related histological changes in these brain tissues. The study was performed on eighteen rats which were fed control (CD) or fish oil supplemented diet (FOD) for 12 months. We investigated the n-3 and n-6 brain FA profile by gas-chromatography analysis. Histomorphometry included the measurement of the quantity of pyramidal cells in the cerebral cortex (layer II-III) and in the hippocampal formation (CA1, CA3 and DG). The number of apoptotic cells (neuron and glial cells) was also calculated separately in three hippocampal areas and in the pyramidal cerebral cortex layer. Rats fed supplemented diet showed a significantly poorer content of the arachidonic acid (AA, 20:4n6) in all brain regions when compared to the control group. Furthermore, the level of the docosahexaenoic acid (DHA, 22:6n3) was significantly higher in the cerebral cortex in fish oil fed rats vs. the control group. The neurons of the pyramidal cortex showed significant changes in cell density in control animals when compared to the group of fish oil fed rats. Furthermore, the number of positive apoptotic cells was significantly higher in the CA1 area and cerebral pyramidal layer in rats fed control diet. Following dietary n-3 fatty acids supplementation, the increase in DHA content in the cerebral cortex resulted in consequential changes in histology of this tissue. The results obtained indicate that dietary intake of fish n-3 fatty acids may reduce the risk of age-related brain impairments.